Understanding First Nations Young Adults' Health Literacy - Rempel, Ebony (Scholarship@Western, 2013)
Relative to non-First Nations, Inuit, and Metis (FNIM) Canadians, FNIM people have poorer health status. A qualitative investigation of the health literacy skill and the health information (HI) needs of young FNIM adults was conducted. Eight single mothers living on-reserve were interviewed. Data analysis generated four main themes along with the subthemes of: (1) Traditional Health (TH), (i) TH Culture Excised, and (ii) Wanting to Know More about TH; (2) HI Needs of First Nations young Mothers; (3) Access to HI, (i) Asking the Doctor / Telehealth (ii) other Female Family and Friends; (4) Online Accessibility, (i) HI Online, (ii) Social Media, and (iii) Navigation and Computer Skills. Although participants expressed a lack of confidence in their computer skills, they did use social media to access HI. While TH practices were valued, there was a lack of understanding and lack of access to TH practices.